New Weapons to Control Bacterial Growth - Villa, Tomas G.; Vinas, Miguel (Springer International Publishing : Imprint: Springer, 2016)
Written by specialists in the different fields, this book presents new perspectives and insights into strategies and weapons to fight microbial infections. It also reviews the "state of the art" of alternative treatment approaches and new therapeutic agents to deal with infections caused by multidrug-resistant microorganisms. In an era of accumulated resistance to current antibiotics, it is vital that this is undertaken without further delay. Aspects discussed include the control of RNA synthesis, the use of bacteriocins or enzybiotics (bacteriophages or purified lysins), the specific control of pathogenic clostridia, the design of new drugs affecting DNA synthesis in bacteria, the use of fecal-matter transplant strategies, the specific control of quorum sensing responses in bacteria, the use of new peptides as antibiotics and new ways to control bacteria that cause cancer, such as Helicobacter pylori cancers.